Identifikasi Senyawa Alkaloid dari Akar Piper sarmentosum Roxb. Ex Hunter dan Uji Aktivitasnya terhadap Jamur Candida albicans - Hartiwi Diastuti; Sadiah Achmad; Enny Ratnaningsih (Fakultas Biologi | Universitas Jenderal Soedirman, 2005)
Piper sarmentosum Roxb. Ex Hunter or “Sirih duduk” has long been used for traditional medicine to cure various diseases, such as fungus infections. The investigation of the bioactive compounds of P. sarmentosum roots has not been carried out. This research was aimed to isolate the bioactive compounds from P. sarmentosum roots. The results showed that methanol extracts of P. sarmentosum roots have an activity on Candida albicans. The separation a bioactive compounds from methanol extracts of P. sarmentosum roots was performed by column chromatography, thin layer chromatography and recrystalizations. The identifications of the bioactive compounds were carried out using ultra violet spectrometry, infrared spectrometry, gas chromatography-mass spectrometry and nuclear magnetic resonance spectrometry. The results indicated that from methanol extracts, an alkaloid compound of piperoylpyrol derivative was 5-hydroxy-5- (3,4-methylenedioxyphenyl)-2-pentenoyl pyrol, could be purely isolated. Examination of bioactivity at concentration 0.10-2.50 mg/ml showed that this compound had an activity on C. albicans.